Measuring spatial migration focusing in Klang Valley, Malaysia / Mohd Fadzil Abdul Rashid and Ishak Ab. Ghani - Abdul Rashid, Mohd Fadzil; Ab. Ghani, Ishak (Universiti Teknologi MARA, Pulau Pinang, 2014)
Internal migration is one of the crucial urban phenomena that affects physical, economic and social aspects of urban planning and development. Many scholars in this area agree that a shortfall of urban planning is due to the difficulty of understanding migration systems in urban areas. Thus, urban planners are obligated to understand spatial migration focusing in urban areas in order to plan of what migration needs. This article attempts to discuss the application of Multiplicative Component Model (MCM) for measuring the migration systems in the Klang Valley region. For the analysis, only three years (period) of migration data (life time migration) are used: years 1980, 1991, and 2000. Life migration data from the 2010 census is still not available. From this application, it is shown that the MCM model has successfully explained the trends and migration distribution in the Klang Valley especially at the macro level.